Calcule o valor de cada expressão numérica:
a) (−7 − 4). (−9 + 2) − (−72 + 2): (−5 − 5) + (−9 − 4 + 6)
b) (−9 − 3): (−1 + 7) − [10 − (−4 − 3)(−5 + 4) + (−36): (−1 − 3)]
c) (−1 − 4)(−10 + 16) − [(−8): (+2) − 7 − (−1)(+5)]
d) (−50): (−5 − 5) − [20 + (−42): (+7) − (−35): (−1 − √16)]
Soluções para a tarefa
Resposta:
a) (-7 - 4). (-9 + 2) - (-72 + 2) : (-5 - 5) + (-9 - 4 + 6)
-11. (-9 + 2) - (-72 + 2) : (-5 - 5) + (-9 - 4 + 6)
-11. (-7) - (-72 + 2) : (-5 - 5) + (-9 - 4 + 6)
-11. (-7) - (-70) : (-5 - 5) + (-9 - 4 + 6)
-11. (-7) - (-70) : (-10) + (-9 - 4 + 6)
-11. (-7) - (-70) : (-10) + (-13 + 6)
-11. (-7) - (-70) : (-10) + (-7)
77 - (-70) : (-10) + (-7)
77 - 7 + (-7)
77 - 7 - 7
70 - 7
63
===============================================================
b) (-9 - 3) : (-1 + 7) - [10 - (-4 - 3) . (-5 + 4) + (-36) : (-1 - 3)]
(-9 - 3) : (-1 + 7) - [10 - (-7) . (-5 + 4) + (-36) : (-1 - 3)]
(-9 - 3) : (-1 + 7) - [10 - (-7) . (-1) + (-36) : (-1 - 3)]
(-9 - 3) : (-1 + 7) - [10 - (-7) . (-1) + (-36) : (-4)]
(-9 - 3) : (-1 + 7) - [10 - 7 + (-36) : (-4)]
(-9 - 3) : (-1 + 7) - [10 - 7 + 9]
(-12) : (-1 + 7) - [10 - 7 + 9]
-12 : 6 - [10 - 7 + 9]
-12 : 6 - [3 + 9]
-12 : 6 - 12
-2 - 12
-14
===============================================================
c) (-1 - 4) . (-10 + 16) - [(-8) : 2 - 7 - (-1) . 5]
(-1 - 4) . (-10 + 16) - [-4 - 7 - (-1) . 5]
(-1 - 4) . (-10 + 16) - [-4 - 7 - (-5)]
(-1 - 4) . (-10 + 16) - [-4 - 7 + 5]
-5 . (-10 + 16) - [-4 - 7 + 5]
-5 . 6 - [-4 - 7 + 5]
-5 . 6 - [-11 + 5]
-5 . 6 - (-6)
-5 . 6 + 6
-30 + 6
-24
===============================================================
d) (-50) : (-5 - 5) - [20 + (-42) : 7 - (-35) : (-1 - √16)]
(-50) : (-5 - 5) - [20 + (-42) : 7 - (-35) : (-1 - 4)]
(-50) : (-5 - 5) - [20 + (-42) : 7 - (-35) : (-5)]
(-50) : (-5 - 5) - [20 + (-6) - (-35) : (-5)]
(-50) : (-5 - 5) - [20 + (-6) - 7]
(-50) : (-5 - 5) - [20 - 6 - 7]
(-50) : (-10) - [20 - 6 - 7]
5 - [20 - 6 - 7]
5 - [14 - 7]
5 - 7
-2